1975
DOI: 10.1093/infdis/132.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Miconazole in Coccidioidomycosis. I. Assays of Activity in Mice and in Vitro

Abstract: Administration of miconazole to mice infected with Coccidioides immitis prevented death in all cases; the infecting doses killed 60%-100% of the untreated animals. The drug's anticoccidioidal influence was also demonstrated by its capacity to limit fungal proliferation in the lungs. The endospore phase of C. immitis, which predominates in lesions, was more susceptible to miconazole than were the saprophytic arthrospore and mycelial phases. The drug was lethal to endospores in vitro in the presence or absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…Van Cutsem and Thienpont (323) demonstrated the efficacy of miconazole given orally or topically against cutaneous infections with T. mentagrophytes, Microsporum canis, and C. albicans in guinea pigs. In another study, all mice given miconazole intramuscularly and subcutaneously 4 days after infection with 50 or 100% lethal doses of Coccidioides immitis were protected, whereas 60 to 100% of the untreated mice succumbed (178). Cultural assays of lung tissue confirmed that the drug limited proliferation of the fungus at that site.…”
Section: Clotrimazolementioning
confidence: 95%
“…Van Cutsem and Thienpont (323) demonstrated the efficacy of miconazole given orally or topically against cutaneous infections with T. mentagrophytes, Microsporum canis, and C. albicans in guinea pigs. In another study, all mice given miconazole intramuscularly and subcutaneously 4 days after infection with 50 or 100% lethal doses of Coccidioides immitis were protected, whereas 60 to 100% of the untreated mice succumbed (178). Cultural assays of lung tissue confirmed that the drug limited proliferation of the fungus at that site.…”
Section: Clotrimazolementioning
confidence: 95%
“…immitis strain Silveira (ATCC 28868), that has been used in many previous studies (2,14,17). However, it is reasonable to monitor periodically the serum levels of amB in patients with coccidioidomycosis so that the intravenous dosage can be adjusted to provide serum levels of 1.0 to 2.0 ug/ml, which appears to suffice for inhibition of C. immitis.…”
Section: Discussionmentioning
confidence: 99%
“…coccidioidomycosis, though recent work has indicated that miconazole may assume a position of some importance (5, 17,31,32). The effectiveness of amB in treating various forms of disseminated coccidioidomycosis of humans has been difficult to assess precisely, though it has proved lifesaving in coccidioidal meningitis.…”
mentioning
confidence: 99%
“…Because of these favorable properties, ketoconazole is currently undergoing clinical investigation in a number of medical centers. A method which has been used for measurement of ketoconazole in serum and other body fluids is tedious and hazardous to perform due to the use of Coccidioides immitis as a test microorganism (3). The present report describes a rapid, simple, very sensitive bioassay for the measurement of ketoconazole in serum, cerebrospinal fluid, and other body fluids alone or in the presence of amphotericin B. several times; then the seeded medium was dispensed into plastic petri dishes (150 by 15 mm) arranged on a level surface.…”
mentioning
confidence: 99%